Avaliação de desempenho no instituto federal de educação, ciência e tecnologia da Paraíba (IFPB): implicações para a aprendizagem organizacional. - Andrade , Rossana Figueirêdo Nunes de (2017)
In the current context of organizations, people need to reflect on their actions by identifying the aspects that need to be developed in order to boost their competencies and improve their performance. In this sense, a professional performance evaluation policy, integrated with other people management systems, can contribute to the reflection-action-reflection process, providing people with a rethinking of their professional practices, in addition to identify their skills gaps, as well as their potentialities. In this way, learning processes can be stimulated to the development of new competencies, which, consequently, promote professional and organizational development. Thus, the present research aimed to identify the implications of the process of performance evaluation of Administrative Technicians in Education for organizational learning at the Federal Institute of Education Science and Technology of Paraíba. To this purpose, the study was based on theoretical references that dealt with the phenomena of performance evaluation and organizational learning, reflecting on the practices, critically, identifying the implications and the negative aspects involved, in order to have a contextual and systemic understanding of the multiple intervening factors in both processes. In terms of methodology, the research is characterized as a field, delimited by the qualitative approach and, based on the objectives, adopted procedures supported by the descriptive, exploratory and documentary typology, using as a data collection instrument the semistructured interview backed by a Guiding questions. For the analysis of the data collected, we used the Content Analysis method according to Bardin (2011), Richardson (1999), Laville and Dionne (1999). The results of the research evidenced that the process of Performance Evaluation (AD), as it is currently being carried out in the IFPB, has a more negative view, in terms of limitations, than positive view, in terms of potential, based on the perception of the managers interviewed. However, AD can be a very important tool for learning, change and development of the public employee, the work team and the entire organization, provided that it is performed correctly, conscientiously and responsibly. In order for AD to exert its full potential to stimulate learning with a focus on change and development, it is necessary that the process be carried out in the correct way, with seriousness and veracity in the information, always seeking the construction of an interactive space, dialogue, feedback and sharing among those involved, in order to enhance their effects in terms of individual and organizational learning.